2013
DOI: 10.1186/1472-6874-13-15
|View full text |Cite
|
Sign up to set email alerts
|

Fractures in women treated with raloxifene or alendronate: a retrospective database analysis

Abstract: BackgroundRaloxifene and alendronate are anti-resorptive therapies approved for the prevention and treatment of postmenopausal osteoporosis. Raloxifene is also indicated to reduce the risk of invasive breast cancer in postmenopausal women with osteoporosis and in postmenopausal women at high risk of invasive breast cancer. A definitive study comparing the fracture effectiveness and rate of breast cancer for raloxifene and alendronate has not been published. The purpose of this retrospective cohort study was to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 26 publications
1
12
0
Order By: Relevance
“…These side effects limit its use in some particular populations. Previous studies demonstrated that raloxifene had statistically significantly lower 18 or similar rates 12,19 of fractures due to decreased BMD in comparison with bisphosphonates. Ellewellyn G. indicated that patients in the raloxifene group believed that their QoL had improved more and had higher treatment satisfaction than patients in the bisphosphonate group 12 .…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…These side effects limit its use in some particular populations. Previous studies demonstrated that raloxifene had statistically significantly lower 18 or similar rates 12,19 of fractures due to decreased BMD in comparison with bisphosphonates. Ellewellyn G. indicated that patients in the raloxifene group believed that their QoL had improved more and had higher treatment satisfaction than patients in the bisphosphonate group 12 .…”
Section: Discussionmentioning
confidence: 94%
“…Considerable attention has been paid to bisphosphonates. This drug benefits the preservation of periprosthetic bone for postmenopausal osteoporosis 17,18 . Although bisphosphonates are safe drugs in most cases, they have numerous side effects, such as gastrointestinal disturbances, arthralgia, elevated erythrocyte sedimentation rate and C-reactive protein, and flu-like illness with symptoms of fatigue, fever, chills, malaise, and myalgia 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a classic antiresorptive biphosphonate, alendronate sodium (ALE) has been frequently prescribed in clinics for the prevention and treatment of postmenopausal osteoporosis [38]. Its role to inhibit normal bone resorption was also confirmed in tail-suspended rats, which resulted in the net bone mass increase [39].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the adverse effects (AEs) of two agents, which would highly provide reference during clinical decision making, were not thoroughly compared in previous meta-analyses. (b) Recently, a large-scaled retrospective study conducted by Foster et al [14] emphasized that after adherent treatment there was a similar risk reduction for the both drugs in both vertebral and nonvertebral fractures of women up to 8 years, which was inconsistent with the previous prospective evidence [6, 12, 13]. (c) There were emerging head-to-head RCTs to evaluate the comparative effectiveness of the two agents, the results of which were mainly limited by the small sample size but those available comparative data should be well summarized and taken into consideration [1521].…”
Section: Introductionmentioning
confidence: 99%